2020
DOI: 10.3389/fbioe.2020.557885
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Bacterial Cellulose for the Development of an Antibacterial Wound Dressing

Abstract: Antibacterial Wound Dressing From Bacterial Cellulose the scratched area after 5 days for both the modified cellulose and the positive control (i.e., keratinocytes growth medium). Overall, the modified hydrogel showed promising features, confirming its potential as an alternative substrate to develop a sustainable, antibacterial and biocompatible wound dressing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 99 publications
(107 reference statements)
2
40
0
Order By: Relevance
“…On the way towards expanding the scale of BC applications, it is crucial to exploit the unique structure and properties of BC to develop novel BC-based nanomaterials with new features. Various functionalization methods for BC-based materials concentrated on the chemical modification or physical coating [57,58]. The macromolecular structure of BC can be controlled by traditional approaches such as the change of cultivation strategy, type of strain, carbon source, and additives [59,60].…”
Section: Product Levelmentioning
confidence: 99%
“…On the way towards expanding the scale of BC applications, it is crucial to exploit the unique structure and properties of BC to develop novel BC-based nanomaterials with new features. Various functionalization methods for BC-based materials concentrated on the chemical modification or physical coating [57,58]. The macromolecular structure of BC can be controlled by traditional approaches such as the change of cultivation strategy, type of strain, carbon source, and additives [59,60].…”
Section: Product Levelmentioning
confidence: 99%
“…These simple recognition peptides are easily incorporated into nanoparticles and can be incorporated into oncolytic viruses and bacteria through genetic modification techniques. Thus, targeting integrins overexpressed or alternatively expressed on the surface of tumorigenic cells represents a feasible strategy for all three modalities of drug delivery discussed within this review [231][232][233][234][235][247][248][249][250][251].…”
Section: Cell Surface Moleculesmentioning
confidence: 99%
“…However, synthetic biology mechanisms can be applied to accomplish genetic modification of organisms to produce nanoparticles, especially exosomes. It is worth noting that most bacterial cell surfaces are charged; therefore, chemical modifications are generally relatively easy [248], nor is using biopolymers or enzymes secreted by oncolytic bacteria as indirect therapeutics [249].…”
Section: Modification and Characterization Of Novel Therapeuticsmentioning
confidence: 99%
“…Several studies have proposed the use of BC with other polymers or molecules, resulting in the development of a new material with optimized properties aimed at its application as a wound dressing, through the addition of silver nanoparticles [ 27 ], chitosan [ 28 ], zinc oxide [ 29 ], titanium dioxide [ 30 ], collagen [ 31 ], and starch [ 32 ]. Recent studies have shown that the changes in the physical structure of BC using chemical modifiers improve the biological properties of the biomaterial, confirming its potential as an alternative material to develop an environmentally-friendly and biocompatible wound dressing, which promotes tissue regeneration [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%